IT PROJECT MANAGEMENT: ADAPTIVE MODELS IN CRISIS CONDITIONS - PETRYK, Maksym; GARAFONOVA, Olga (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article explores the transformation of project management practices in the IT sector in response to crisis situations, with a specific focus on Ukraine during the full-scale war. The war has presented Ukrainian IT companies with numerous challenges, including disrupted infrastructure, forced relocations, cybersecurity threats, power outages, and workforce stress due to constant psychological pressure and mobilization. In this context, traditional linear project management approaches have proven insufficient to cope with the heightened uncertainty and instability. Therefore, many organizations have shifted towards adaptive models such as Agile, Scrum, Kanban, and hybrid frameworks that allow for flexibility, iterative planning, and rapid feedback loops. The study analyses how Ukrainian IT teams reorganized their operations under stress: shortening sprint cycles, decentralizing decision-making, adopting asynchronous communication models, and relying more heavily on cloud infrastructure and tools such as Jira, Trello, Slack, and Confluence. The role of psychological resilience and team support systems is emphasized, particularly through initiatives like mental health programs, mentorship sessions, and the implementation of “no-meeting days.” Empirical data from over 15 Ukrainian companies illustrates the critical success factors for project management during crises: flexible workload distribution, horizontal leadership structures, agile risk management, and digital maturity. This paper contributes to the field by contextualizing agile project management within an active war zone and offers practical recommendations for companies worldwide facing high-risk and high-volatility environments. It emphasizes the importance of cultivating antifragility in teams and systems — turning crises into opportunities for structural evolution and organizational learning. The findings are relevant not only for project managers and executives but also for researchers seeking to understand innovation processes in turbulent settings.
Keywords: innovation; IT companies; management; war; adaptation; R&D; digital transformation